Gdy u nas w KP była 27. Dywizja… . Przypadek akowca na etacie Komitetu Powiatowego PZPR - Czarnota, Tomasz (Komunizm: System - Ludzie - Dokumentacja, 2015)
Stalinism in Poland were characterized by, among other things, taking place within the Polish United Workers' Party purification processes its ranks of "enemies". Especially with "reactionaries" type of ex-Home Army soldiers. One of them was Zygmunt Gnieciak (1925-1989). Born in Rozyn (Volyn), in 1943-1944 he served in the 27th Volyn Home Army Infantry Division. After its disarmed by the Soviets, was a soldier of WP / WOP(until 1946). Then he worked in power station in Słubice. At the news of settling his family repatriated for Hrubieszow came to the area and started his own family. Soon he took a job political instructor at the District Headquarters of the General Organization "Service to Poland" and then in the District Committee of the Communist Party in Hrubieszow(1949-1951). Factual material indicates that as his clerk, chief of human resources’ department and head of the propaganda department secretly led a double play. Was to use positions in the party to sabotage its various actions. After nearly two years, perhaps for fear of being discovered he revealed that he was once a member of the Home Army. At the same time concealing his role he played in KP Polish United Workers' Party in Hrubieszow. In an atmosphere of dismay that the partyapparatus employed in the former “bandit”, district leadership the Communist Party removed him from his post. But he did not suffer serious consequences beyond throwing their jobs and driven out of Hrubieszow. Not escaped prison in 1953. Was sentenced to a year in prison for lack of managerial supervision of the company buying fruits and vegetables in Chelm, which was then the director. Since the mid 50s to mid 80s. of XXth century he worked in mills and factories fruit andvegetable industry in the counties of Chelm and Hrubieszow.